Importance of providing of economic stability withdevelopment of agroindustrial complex for translation. (Journal of Economic Research & Business Administration, 2016)
The article deals with the economic role of agro-industrial complex in the context of globalization. Special attention is paid to national and international experience in the development of agro-industrial complex. Agro-industrial complex is the main area of high potential of the economy in the country, and has great possibilities. Now, about 43, 0 percent of the people are about one third of the economically active population.Agribusiness is a common production system total capital and develops according to the law of the system. In many cases, the agribusiness changes of consumer goods production to the manufacturing sector of economic resources. Thus, it is not only the production. It is also the environment of the population. And the level of agricultural production has a direct impact on the state of food security in the country. Now, food safety has become a global aspect in the context of globalization, therefore, subject of the article is very relevant.
Keywords: Agriculture; the international not food market; diversity; agro-industrial integration; a food security.